Evaluating the utility of archaeological index fossils: Optically-stimulated luminescence dating of Fort Ancient Pottery at the Hahn Site. (October 2017) - Cook, Robert A.; Sakai, Sachiko; Genheimer, Robert A.
Abstract: One of the most common undertakings in archaeology is to establish absolute temporal sequences of artifacts. Once such tasks are completed, items become index fossils that serve to inform on chronology often in the absence of absolute dates. While such chronologies are best constructed through the direct dating of the items in question, this is too rarely the case. In contrast, various associations are made between the objects and dated organic materials. Change is often then seen as being abrupt, with important consequences for archaeological interpretation. Here we use optically-stimulated luminescence (OSL) dating to directly examine this issue with a case study involving the timing of Anderson-style and Madisonville-style pottery, two of the main styles of Fort Ancient pottery that are seen as reliably separating later (after 1400 CE) from earlier periods (ca. 1000–1400 CE). This temporal distinction is best expressed by the common designation of sites with both pottery styles as being temporally multicomponent. However, it has been noted by some researchers that these styles may overlap to a significant degree, based on associated radiocarbon dates. Our findings confirm this suspicion, with direct evidence through OSL dating with samples from the Hahn site. Highlights: Directly dating pottery is needed to better understand past human behavior. Optically-stimulated luminescence (OSL) dating is well-suited to this task. US Midwest case shows considerable temporal overlap between two pottery types long thought to be relatively discrete. More research is needed to understand social implications but likely involves arrival of some new people in the region.